Precarious bodies in Henry James's What Maisie Knew. Issue 10 (26th November 2019) - Rivkin, Julie
ABSTRACT: A critical history of treating consciousness as incorporeal in Henry James has been succeeded by an examination of embodied consciousness in his fiction, including cognitive, feminist materialist, and neurobiological approaches. This study shifts the focus in a political direction, reading What Maisie Knew as a study of how power conditions the experience of embodiment. Experiencing the divorce as a rupture that distorts her sense of bodily integrity, Maisie exhibits a heightened sensitivity to the precarious bodies of others. This sensitivity can result in either increased empathy with others or xenophobia, and the novel exhibits both. Judith Butler's work in Precarious Life informs these reflections on precarious bodies in What Maisie Knew .